Impact of INM practices on system productivity and soil health of pearlmillet-mungbean cropping system in Inceptisols of India - YADAV, MANISH; JADAV, N.J.; KUMAR, DILEEP; VASHISHT, B.B.; KUMAR, ARUN; SINGH, SAMAR PAL (Journal of Soil and Water Conservation, 2024)
Pearlmillet and mungbean are important crops in India, contributing to food security and providing valuable nutrients additionally the cereal legume cropping system sustain the soil health. However, their productivity is often limited by low soil fertility and inadequate nutrient management. This study aimed to quantify the direct effect of INM on grain yield of pearlmillet and the residual effect on the productivity of mungbean and soil properties. In this background, a field experiment was conducted at the Agronomy Farm of Anand Agricultural University, Gujarat, India to study the effect of INM practices on system productivity and soil health of pearlmillet-mungbean cropping system. The experiment comprised of ten different combinations of organic and inorganic fertilizers with or without liquid biofertilizer and laid-out in randomized block design with four replications. Results showed that the treatment CF1FYM15BNP (100% RDF + 15 t FYM + liquid biofertilizer contains Azotobacter + phosphorus solubilizing bacteria) had the highest grain yield of 3105 kg ha-1 for pearlmillet, 1478 kg ha-1 of mungbean and system productivity of 8.05 t ha-1 in pearlmillet-mungbean system. A notable increment organic carbon content (24.9%) and water holding capacity (35.0%) were noticed under application of CF1FYM15BNP as compared to control treatment (CF1). Soil analysis revealed improvements in soil properties such as pH decreased by 0.5 units, available NPK increased by 30-65%, and DTPA micronutrients (Fe, Mn, Zn and Cu) increased by 26-73% due to direct and residual effect of organics, inorganic fertilizers and liquid biofertilizer.